(untitled) (International Journal of Advanced Research in Computer Science, 2017)
Cryptography and steganography are the 2 popular methods available to provide security. The objective of cryptography is data protection and the objective of steganography is secret communication. Cryptography converts the data into cipher text that can be in unreadable format to normal user where steganography hides the existence of message by embedding data into some other digital media. Both of them has their own vulnerabilities. Crypto-steganography combination overcomes each other’s weakness and make difficult for intruders to attack or steal sensitive information. This paper focus on the strength of combining cryptography with steganography and various works in the area of combination of these 2 techniques are discussed. Keywords: Cryptography; Steganography; Cipher, Stego image; Advanced Encryption Standard; Least Significant Bit